2001
DOI: 10.1143/jjap.40.l62
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Acoustic Energy Loss in Surface Acoustic Wave Filters Using Grating Waveguides

Abstract: The acoustic energy loss in surface acoustic wave filters using grating waveguides is investigated experimentally. The propagation loss in the waveguide formed on a ST-cut quartz with aluminum grids, which have the period detuned from that of the Bragg condition, is evaluated to be small as 2 × 10 −3 dB/wavelength. However, it is revealed that the extra energy loss arises with a short waveguide length and before surface acoustic waves (SAWs) launched by the interdigital transducer (IDT) enter the waveguide. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In the second year, in 2001, Jun Tsutsumi studied the acoustic energy loss of the grating waveguide SAW filter. Based on the experiment, it was concluded that by increasing the thickness of the aluminum film, the insertion loss of the mirror filter using the SAW grating waveguide could be reduced by 2 dB [ 73 ]. For the layered surface acoustic wave device, it is not only affected by the substrate, but also affected by the interdigitated metal electrodes.…”
Section: Saw Filter Technologymentioning
confidence: 99%
“…In the second year, in 2001, Jun Tsutsumi studied the acoustic energy loss of the grating waveguide SAW filter. Based on the experiment, it was concluded that by increasing the thickness of the aluminum film, the insertion loss of the mirror filter using the SAW grating waveguide could be reduced by 2 dB [ 73 ]. For the layered surface acoustic wave device, it is not only affected by the substrate, but also affected by the interdigitated metal electrodes.…”
Section: Saw Filter Technologymentioning
confidence: 99%